E-LEARNING UNTUK SEKOLAH DASAR SWASTA TAMANSISWA MATRAMAN BERBASIS WEB - Endah Elfayani; Fauziyah Fauziyah; Alexius Ulan Bani (LPPM Universitas Bina Bangsa, 2022)
Tamansiswa Elementary School was founded on July 3, 1922, which was founded by Raden Mas Soewardi Soeryanagih or commonly known as Ki Hajar Dewantara. Tamansiswa Elementary School is one of the private schools that is not only used for learning but also for fighting for culture and creating a more literate society by developing education for the welfare of the nation. The method used to complete this thesis is the method of interview, observation and literature study. The system model used is Undifield Modeling Language (UML) using the PHP programming language and MySql database. This e-learning information system was created so that the private elementary school Tamansiswa Cab Matraman implements e-learning so that its students can still carry out the teaching and learning process without being constrained by the place and time when there is a dangerous virus attack